The Three‐Dimensional Bow Shock of Mars as Observed by MAVEN. Issue 6 (5th June 2018) - Gruesbeck, Jacob R.; Espley, Jared R.; Connerney, John E. P.; DiBraccio, Gina A.; Soobiah, Yasir I.; Brain, David; Mazelle, Christian; Dann, Julian; Halekas, Jasper; Mitchell, David L.
Abstract: The Martian magnetosphere is a product of the interaction of Mars with the interplanetary magnetic field and the supersonic solar wind. The location of the bow shock has been previously modeled as conic sections using data from spacecraft such as Phobos 2, Mars Global Surveyor, and Mars Express. The Mars Atmosphere and Volatile EvolutioN (MAVEN) mission spacecraft arrived in orbit about Mars in November 2014 resulting in thousands of crossings to date. We identify over 1, 000 bow shock crossings. We model the bow shock as a three‐dimensional surface accommodating asymmetry caused by crustal magnetic fields. By separating MAVEN's bow shock encounters based on solar condition, we also investigate the variability of the surface. We find that the shock surface varies in shape and location in response to changes in the solar radiation, the solar wind Mach number, dynamic pressure of the solar wind, and the relative local time location of the strong crustal magnetic fields (i.e., whether they are on the dayside or on the nightside). Plain Language Summary: A shock wave forms when the supersonic solar wind flows around objects in the Solar System. We studied the shape of this bow shock at Mars; the obstacle to the solar wind at Mars is the upper atmosphere and the patches of the crust that have localized strong magnetic fields. Previous studies have shown that the Martian bow shock can change due to changing solar wind or the location of crustal magnetic fields. Two‐dimensional equations have been used to create mathematical models of the Martian bow shock, but they have implicit assumptions about the symmetry of the surface. Using over 2 years of observations from Mars Atmosphere and Volatile Evolution Mission, we have used a general surface equation to model the Martian bow shock fully in three‐dimensions, which is able to represent the asymmetric shape of the surface. We find that while changes in the solar wind change the size of the Martian bow shock, the location of the crustal fields are most important factor in producing the asymmetric shape of the shock. Investigating how the bow shock varies under different solar wind conditions can be important toward understanding of how the Sun impacts the Martian magnetosphere that can drive important processes, such as atmospheric. Key Points: Using MAVEN observations, we present a model of the Martian bow shock that unlike previous conic models is fully three‐dimensional The bow shock is asymmetric, occurring further from the planet in the Southern Hemisphere where the strongest crustal magnetic fields are The bow shock is variable; its location and shape are influenced by solar radiation, solar wind, and location of crustal fields